PRACTICAL APPLICATIONS OF HYDROGEN FUEL AND ITS TECHNOLOGICAL PROSPECTS (Ustozlar uchun, 2025)
This paper investigates hydrogen fuel production technologies using solar energy. The study analyzes thermochemical water decomposition under high temperatures achieved by concentrating solar power systems. Results indicate that at temperatures between 1000°C and 1500°C, hydrogen yield increases while energy losses decrease due to the optimization of concentrator geometry and heat recovery mechanisms.